The immunoglobulin M-degrading enzyme of Streptococcus suis, IdeSsuis, is a highly protective antigen against serotype 2. Issue 19 (5th May 2015) - Seele, Jana; Hillermann, Lena-Maria; Beineke, Andreas; Seitz, Maren; von Pawel-Rammingen, Ulrich; Valentin-Weigand, Peter; Baums, Christoph G.
Abstract: Streptococcus suis ( S. suis ) is a major porcine pathogen causing meningitis, arthritis and several other pathologies. Recently, we identified a highly specific immunoglobulin M degrading enzyme of S. suis, designated Ide Ssuis, which is expressed by various serotypes. The objective of this work was to access the immunogenicity and protective efficacy of a recombinant vaccine including Ide Ssuis . Vaccination with rIde Ssuis elicited antibodies efficiently neutralizing the IgM protease activity. Importantly, 18 piglets vaccinated with rIde Ssuis alone or in combination with bacterin priming were completely protected against mortality and severe morbidity after S. suis serotype 2 challenge. In contrast, 12 of the 17 piglets either treated with the placebo or primed with the bacterin only, succumbed to S. suis disease. Immunity against Ide Ssuis was associated with increased killing of S. suis wt in porcine blood ex vivo leading to a tenfold difference in the bacterial survival factor in blood of placebo-treated and rIde Ssuis -vaccinated piglets. In conclusion, the results of this study indicate that rIde Ssuis is a highly protective antigen in pigs.